Wolbachia infection in populations of the coniferous forest pest Dendrolimus superans sibiricus Tschetverikov, 1908 (Lepidoptera: Lasiocampidae) - M. A. Yudina; V. V. Dubatolov; R. A. Bykov; Yu. Yu. Ilinsky (Вавиловский журнал генетики и селекции)
Siberian silk moth (Dendrolimus superans sibiricus) is a very dangerous pest of coniferous trees, in particular, larch and various pine species. Outbreaks of this pest lead to defoliation and forest destruction in a vast area of the Asian part of Russia. Many biological agents, such as viruses, pathogenic microorganisms and parasitoids, prevent the growth of Siberian silk moth population. Here we consider non-pathogen symbiotic Wolbachia bacteria, which are transovarially transmitted between specimens from mother to offspring. This symbiont has an ability to affect biology of its host. In theory, Wolbachia can prevent the growth of population size or induce it, which determines the focus of interest in Wolbachia-host investigation. Two samples from a Siberian silk moth population collected in 2014 and 2016 in Khabarovsk area were studied for Wolbachia infection. We found a high Wolbachia prevalence in the population of Siberian silk moth, in particular, the sample of 2014 was totally infected and the sample of 2016 had 90 % infected specimens. There were at least two distinct Wolbachia strains reveled by analysis of two loci from the MLST protocol, namely f tsZ-36, f bpA-4 and f tsZ-22, f bpA-9. In this study, a possible role of Wolbachia in the symbiotic association with Siberian silk moth and general ways of investigation of this symbiosis are discussed.